Experimental analysis of DI diesel engine using dual biofuel blended with diesel. Issue 4 (20th March 2020) - Senthil Kumar, J.; Ramesh Bapu, B. R.
ABSTRACT: In recent years, biodiesel has become more attractive as an alternative fuel for diesel engines because of its environmental benefits and the fact is that it is made from renewable resources. The role of biodiesel is not to replace petroleum diesel, biofuels help to improve the economical growth and positive impacts on the environment. The main purpose of this research is to reduce the emission such as carbon monoxide (CO), nitrogen oxides (NOX ), hydrocarbons (HC) and carbon dioxide (CO2 ). And to increase the performance characteristics such as break thermal efficiency (BTE), specific fuel consumption (SFC) of diesel engines. Here we used dual biofuel (lemongrass oil plus mint oil) blended with diesel and cerium oxide is added as an additive and undergone the test of engine performance and emission parameters of diesel. The measuring parameters are BTHE, specific fuel conception, CO2, CO, NOx and HC.